Preventive education on adolescent idiopathic scoliosis in junior high school students at Surakarta - Alinda Nur Ramadhani; Dea Linia Romadhoni (Community Empowerment, 2024)
Adolescent idiopathic scoliosis (AIS) is a structural disorder of the vertebrae characterized by vertebral curvature exceeding 10°, commonly identified in children aged 10-18 years. Several contributing factors for AIS include genetic factors, abnormalities in connective tissue and skeletal muscles, biomechanical factors, and the use of school bags with associated weight. The primary issue identified from the preliminary study is the relatively high AIS rate, reaching 10.2%, with no previous preventive education programs implemented for students. The targeted participants for this program are students from Muhammadiyah Middle School 5 and Muhammadiyah Middle School 7 in Surakarta. The team conducted AIS prevention health education sessions in April-May 2023 for students aged 12-15 years. The educational activities involved the use of informative materials such as pocket books and videos, covering topics like the definition of Adolescent Idiopathic Scoliosis, physical examination methods for AIS, and preventive measures through posture correction exercises and the proper use of school bags.Results from the influence test, employing the Paired Sample T-Test, indicate a Sig. (2-tailed) value of 0.023. This implies a significant difference in the average knowledge level before and after receiving education on AIS prevention.